Interactions between calcium‐induced arrhythmia triggers and the electrophysiological–anatomical substrate underlying the induction of atrial fibrillation - Colman, Michael A.; Varela, Marta; MacLeod, Rob S.; Hancox, Jules C.; Aslanidi, Oleg V. (The Journal of physiology, 2024)
Atrial fibrillation (AF) is the most common cardiac arrhythmia and is sustained by spontaneous focal excitations and re‐entry. Spontaneous electrical firing in the pulmonary vein (PV) sleeves is implicated in AF generation. The aim of this simulation study was to identify the mechanisms determining the localisation of AF triggers in the PVs and their contribution to the genesis of AF. A novel biophysical model of the canine atria was used that integrates stochastic, spontaneous subcellular Ca2+ release events (SCRE) with regional electrophysiological heterogeneity in ionic properties and a detailed three‐dimensional model of atrial anatomy, microarchitecture and patchy fibrosis. Simulations highlighted the importance of the smaller inward rectifier potassium current (IK1) in PV cells compared to the surrounding atria, which enabled SCRE more readily to result in delayed‐afterdepolarisations that induced triggered activity. There was a leftward shift in the dependence of the probability of triggered activity on sarcoplasmic reticulum Ca2+ load. This feature was accentuated in 3D tissue compared to single cells (Δ half‐maximal [Ca2+]SR = 58 μM vs. 22 μM). In 3D atria incorporating electrical heterogeneity, excitations preferentially emerged from the PV region. These triggered focal excitations resulted in transient re‐entry in the left atrium. Addition of fibrotic patches promoted localised emergence of focal excitations and wavebreaks that had a more substantial impact on generating AF‐like patterns than the PVs. Thus, a reduced IK1, less negative resting membrane potential, and fibrosis‐induced changes of the electrotonic load all contribute to the emergence of complex excitation patterns from spontaneous focal triggers. Key points Focal excitations in the atria are most commonly associated with the pulmonary veins, but the mechanisms for this localisation are yet to be elucidated. We applied a multi‐scale computational modelling approach to elucidate the mechanisms underlying such localisations. Myocytes in the pulmonary vein region of the atria have a less negative resting membrane potential and reduced time‐independent potassium current; we demonstrate that both of these factors promote triggered activity in single cells and tissues. The less negative resting membrane potential also contributes to heterogeneous inactivation of the fast sodium current, which can enable re‐entrant‐like excitation patterns to emerge without traditional conduction block. figure legend Left: probability of cellular trigger activity or tissue focal excitation (PTA) as a function of sarcoplasmic reticulum load ([Ca2+]SR) in isolated cells from the right atrium (RA) and pulmonary veins (PV) and in homogeneous (all cells are modelled as RA) and heterogeneous 3D tissue models. The cellular differences are enhanced in 3D, leading to a large shift in the half‐maximal [Ca2+]SR observed (Δ[Ca2+]SR50). Right: temporal snapshots showing the membrane potential (Vm) in the 3D atria, corresponding to a focal excitation originating from the right pulmonary vein.